2018
DOI: 10.1002/cncr.31318
|View full text |Cite
|
Sign up to set email alerts
|

Salvage treatment using carbon ion radiation in patients with locoregionally recurrent nasopharyngeal carcinoma: Initial results

Abstract: BACKGROUNDReirradiation for locoregionally recurrent nasopharyngeal carcinoma (NPC) after a definitive dose of radiotherapy (RT) is challenging and usually associated with severe toxicities. Intensity‐modulated carbon ion RT (IMCT) offers physical/biologic advantages over photon‐based intensity‐modulated RT. Herein, the authors report their initial experience of IMCT in previously irradiated patients with locoregionally recurrent NPC.METHODSPatients with locoregionally recurrent, poorly differentiated or undif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 33 publications
2
87
1
Order By: Relevance
“…The cumulative rates of acute and late severe (≥ grade III) side effects after CIR were acceptable at 1.8% and 14.3%, respectively. Prior studies on re-irradiation of HNC with carbon ions reported similar toxicity profiles [6,23,24]. However, the distribution of re-irradiation sites in our assessment was quite different from those of prior studies on CIR in recurrent HNC.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…The cumulative rates of acute and late severe (≥ grade III) side effects after CIR were acceptable at 1.8% and 14.3%, respectively. Prior studies on re-irradiation of HNC with carbon ions reported similar toxicity profiles [6,23,24]. However, the distribution of re-irradiation sites in our assessment was quite different from those of prior studies on CIR in recurrent HNC.…”
Section: Discussioncontrasting
confidence: 68%
“…Hayashi et al [21] reported absolute dose constraints at CIR of 30 Gy (RBE) for the brainstem and spinal cord and 40 Gy (RBE) for the optic system. Hu et al [6] assumed a recovery from the previous photon radiotherapy set at 70%, independent of the RT interval. Consequently, the CTV was reduced if it was close to OAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite its potential significance, to our knowledge supporting data investigating the value of cfEBV DNA for disease surveillance are limited; relevant studies mainly have focused on cfEBV DNA prognostication before and in the middle of treatment . Generally, the detection of early recurrent and/or metastatic disease is crucial for better salvage results in patients with NPC because those individuals with early‐stage recurrent disease and a low tumor burden usually have higher treatment response and survival rates . Conventional workups, including physical and imaging examinations, have limited sensitivity and accuracy in diagnosing tumor recurrence early.…”
Section: Introductionmentioning
confidence: 99%